2002
DOI: 10.1016/s0016-7037(01)00759-1
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Cs+ to micaceous subsurface sediments from the Hanford site, USA

Abstract: The sorption of Cs ϩ was investigated over a large concentration range (10 Ϫ9 -10 Ϫ2 mol/L) on subsurface sediments from a United States nuclear materials site (Hanford) where high-level nuclear wastes (HLW) have been accidentally released to the vadose zone. The sediment sorbs large amounts of radiocesium, but expedited migration has been observed when HLW (a NaNO 3 brine) is the carrier. Cs ϩ sorption was measured on homoionic sediments (Na ϩ , K ϩ , Ca 2ϩ ) with electrolyte concentrations ranging from 0.01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
291
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(333 citation statements)
references
References 38 publications
38
291
0
3
Order By: Relevance
“…In particular, our mechanistic interpretation of the competitive ion-exchange of radiocaesium, ammonium, and potassium on illite is consistent with (in situ) observations of reversible sorption behaviour of radiocaesium in aquatic sediments (Evans et al, 1983;Smith and Comans, 1996;Comans, 1999), as well as the observed persistence of this radionuclide in water and food products (fish and vegetation) for Table 1. many years following the Chernobyl accident (Smith et al (2000) discuss the relationship between radiocaesium sorption reversibility on illite and uptake in food products in more detail). It also explains the recent observations by Zachara et al (2002) of incomplete exchange of caesium against 0.1 mol/L KNO 3 on Na-saturated micaceous subsurface sediments from the Hanford site after only short caesium adsorption times.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In particular, our mechanistic interpretation of the competitive ion-exchange of radiocaesium, ammonium, and potassium on illite is consistent with (in situ) observations of reversible sorption behaviour of radiocaesium in aquatic sediments (Evans et al, 1983;Smith and Comans, 1996;Comans, 1999), as well as the observed persistence of this radionuclide in water and food products (fish and vegetation) for Table 1. many years following the Chernobyl accident (Smith et al (2000) discuss the relationship between radiocaesium sorption reversibility on illite and uptake in food products in more detail). It also explains the recent observations by Zachara et al (2002) of incomplete exchange of caesium against 0.1 mol/L KNO 3 on Na-saturated micaceous subsurface sediments from the Hanford site after only short caesium adsorption times.…”
Section: Discussionsupporting
confidence: 77%
“…These results indicate that the desorption reaction is still far from equilibrium after 8 weeks of reaction in 1 mol/L NH 4 Ac. Incomplete exchange of caesium against 0.1 mol/L KNO 3 after only short caesium adsorption times (0.5 d) has also been observed by Zachara et al (2002) for Na-saturated micaceous subsurface sediments from the Hanford site.…”
Section: Radiocaesium Sorption and Desorption On K- Na- And Nh 4 -Imentioning
confidence: 71%
See 1 more Smart Citation
“…This was considered to be due to a slow and continued release of K from mica through the weathering process. Another reason might be due to high fixing capacity of waste mica for cesium (Zachara et al, 2002;Thiry et al, 2005;Sreenivasa Chari, 2010). The data revealed that soil type significantly influenced the 134 Cs transfer factors.…”
Section: Effect Of Waste Mica On Transfer Factors Of 134 Cs To Spinacmentioning
confidence: 99%
“…In the case of caesium, the presence of frayed edge sites (FES) in illite is a powerful sink for this element [4,5]. Co-precipitation of strontium with calcite is also a relevant retention mechanism in the till environment.…”
Section: Retention Processesmentioning
confidence: 99%